Low Contrast Oil Reservoir Evaluation Method Based on Continuous Conductive Channel Calculation - ZHANG Meiling; ZHAO Jiahui; XIONG Kui; WANG Shuangquan (Cejing jishu)
The interpretation of low contrast oil layers with low resistivity has always been a difficult problem in well log evaluation. The situation where the resistivity of the high-yield oil layer in the Weizhou formation of the Fushan depression is comparable to that of the water layer seriously affects the calculation of reservoir reserves. The clay cation exchange model is an effective evaluation model for low resistivity oil layers, but it is difficult to explain the significant differences in clay types and contents in low resistivity oil layers of the Weizhou formation. Based on the principle of electric field equivalent circuit, a confined water connected conduction model is constructed, and the equivalent resistivity of the model is calculated using finite element numerical techniques and Ohm's Law. Selecting actual low contrast oil layers with similar physical properties and significant differences in clay types in the Weizhou formation, the cation exchange model and bound water connected conduction model are used for calculation. It is found that the resistivity calculated by the bound water connected conduction model matched better with the actual well measurement values, which could more effectively explain the low contrast oil layers in the Weizhou formation and lay a reliable basis for the reserve evaluation of the Weizhou formation reservoir. The bound water connected conduction model starts from the basic theory of electric fields and is not limited by complex microscopic phenomena such as clay types and their distribution in rock layers. This method has universality and promotional value.